EVALUASI KEANDALAN SISTEM DISTRIBUSI 20 KV DENGAN MENGGUNAKAN PENGGABUNGAN METODE SECTION TECHNIQUE DAN RELIABILITY INDEX ASSESSMENT (RIA) DI PT PLN (PERSERO) ULPPORONG PADA PENYULANG JIKEN - Asyhari, Ahmad Rizky; Utomo, Teguh; Wibawa, Unggul (Jurnal Mahasiswa TEUB, 2025)
The need for the availability of reliable and efficient electrical energy is expected by the community as consumers. To find out how reliable and efficient a system is in supplying electrical energy to customers, it is necessary to analyze the reliability of the system. Distribution system reliability analysis can be done using several methods such as Section Technique and Reliability Index Assessment (RIA). The purpose of combining the Section Technique and RIA methods is to combine or sum up the parameters of the sustained failure rate and also the momentary failure rate. The combination of these two methods aims to complement the Section Technique method which only uses the sustained failure rate parameter. This study aims to determine the reliability index value of the Jiken Feeder of PT PLN (Persero) ULP Porong. In addition, this study will also calculate the value of economic losses received by PT PLN (Persero) ULP Porong based on the amount of Energy Not Supplied during a disturbance. To determine the reliability index value of Jiken Repository, several methods will be carried out, namely manual calculation using the Section Technique method and also a combined method (Section Technique - RIA), RIA and simulation using ETAP 19.0.1 software. The final result of the reliability index value will then be compared with the provisions of SPLN No. 59 of 1985, which shows that Jiken is categorized as unreliable because its reliability index value is above the provisions of SPLN No. 59 of 1985.Keywords : Section Technique, Combined Method, ETAP, Energy Not Supplied, Economic Loss